2008
DOI: 10.1016/j.neuropsychologia.2008.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Does lateral parietal cortex support episodic memory?

Abstract: Although neuroimaging and human lesion studies agree that the medial parietal region plays a critical role in episodic memory, many neuroimaging studies have also implicated lateral parietal cortex, leading some researchers to suggest that the lateral region plays a heretofore underappreciated role in episodic memory. Because there are very few extant lesion data on this matter, we examined memory in six cases of focal lateral parietal damage, using both clinical and experimental measures, in which we distingu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
177
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(222 citation statements)
references
References 106 publications
43
177
0
Order By: Relevance
“…This is consistent with neuropsychological studies showing that patients with parietal lesions reported ABMs that lacked episodic richness (Berryhill et al, 2007;Davidson et al, 2008). With regard to the role of the parietal cortex in episodic memory, the current findings can be interpreted in light of the dual attentional processes hypothesis (Cabeza, 2008;Ciaramelli et al, 2008), which distinguishes between the role of dorsal and ventral parietal regions.…”
Section: Neuropsychological Predictors Of the Proportion Of Internal supporting
confidence: 91%
“…This is consistent with neuropsychological studies showing that patients with parietal lesions reported ABMs that lacked episodic richness (Berryhill et al, 2007;Davidson et al, 2008). With regard to the role of the parietal cortex in episodic memory, the current findings can be interpreted in light of the dual attentional processes hypothesis (Cabeza, 2008;Ciaramelli et al, 2008), which distinguishes between the role of dorsal and ventral parietal regions.…”
Section: Neuropsychological Predictors Of the Proportion Of Internal supporting
confidence: 91%
“…However, this latter hypothesis does not clearly account for the results of meta-analyses showing that, within the parietal lobe, familiarity is preferentially associated with the superior parietal cortex whereas recollection is preferentially associated with the inferior parietal cortex (Kim, 2010;Skinner and Fernandes, 2007). It has recently been proposed that the parietal lobe supports the subjective experience of recollection or a similar aspect of recollection, the feeling of confidence (Ally et al, 2008;Berryhill et al, 2007;Davidson et al, 2008;Hayes et al, 2011;Slotnick, 2010). Simons et al (2010) reported that patients with bilateral parietal lesions have impaired subjective recollection but preserved bottom-up attention processes during memory tasks.…”
Section: Functional Connectivity During Associative Cermentioning
confidence: 98%
“…Recently, memory researchers have also turned their attention to the role of PPC in cognition because human neuroimaging experiments have consistently revealed PPC activity during episodic retrieval (Wheeler and Buckner 2004;Wagner et al 2005;Cabeza et al 2008;Ciaramelli et al 2008;Vilberg and Rugg 2008b;Olson and Berryhill 2009). Moreover, studies of human patients with lesions to PPC have revealed subtle, but significant, memory impairments (Berryhill et al 2007;Davidson et al 2008;Berryhill et al 2010;Ciaramelli et al 2010;Drowos et al 2010; Simons et al 2010, cf. Ally et al 2008;Haramati et al 2008;Simons et al 2008).…”
Section: Introductionmentioning
confidence: 99%